Access-Site Complications in Transfemoral Neuroendovascular Procedures: A Systematic Review of Incidence Rates and Management Strategies. Issue 4 (4th May 2020) - Oneissi, Mazen; Sweid, Ahmad; Tjoumakaris, Stavropoula; Hasan, David; Gooch, M Reid; Rosenwasser, Robert H; Jabbour, Pascal
Abstract: BACKGROUND: The femoral artery is the most common access route for cerebral angiography and neurointerventional procedures. Complications of the transfemoral approach include groin hemorrhages and hematomas, retroperitoneal hematomas, pseudoaneurysms, arteriovenous fistulas, peripheral artery occlusions, femoral nerve injuries, and access-site infections. Incidence rates vary among different randomized and nonrandomized trials, and the literature lacks a comprehensive review of this subject. OBJECTIVE: To gather data from 16 randomized clinical trials (RCT) and 17 nonrandomized cohort studies regarding femoral access-site complications for a review paper. We also briefly discuss management strategies for these complications based on the most recent literature. METHODS: A PubMed indexed search for all neuroendovascular clinical trials, retrospective studies, and prospective studies that reported femoral artery access-site complications in neurointerventional procedures. RESULTS: The overall access-site complication rate in RCTs is 5.13%, while in in non-RCTs, the rate is 2.78%. The most common complication in both groups is groin hematoma followed by access-site hemorrhage and femoral pseudoaneurysm. On the other hand, wound infection was the least common complication. CONCLUSION: The transfemoral approach in neuroendovascular procedures holds risk for several complications. This review will allow further studies to compare access-site complications between the transfemoral approach and other alternative access sites, mainly the transradial approach, which is gaining a lot of interest nowadays. Graphical Abstract: